The Potential of Natural Based-Skincare Cosmetic Ingredients for Naturally Glowing Skin - Oktaviani, Dede Jihan; Susilawati, Yasmiwar; Tjitraresmi, Ami; Zuhrotun, Ade (Borneo Journal of Pharmacy, 2023)
The use of skincare products is the primary need in modern society. There is an increase in awareness of maintaining beauty and healthy skin, as well as the desire to have naturally glowing, healthy skin, which is in line with the rise in the use of cosmetics, especially skincare products. Nature provides many plants and marine resources (such as algae) that can be utilized as essential ingredients for cosmetics preparations with various benefits such as cleansers, toners, moisturizers, and sun protectors, a primary series of skincare products to gain naturally glowing, healthy skin. This review aims to provide information about plants and marine algae that can be used as skincare ingredients, their phytochemical contents, and their function in cosmetics to achieve naturally glowing skin. Various plants and marine algae categorized based on their benefits as skincare have great potential to be developed as ingredients in cosmetic preparations. The content of phytochemical compounds in these plants and marine algae supports these benefits. Each skincare category has major phytochemical compounds that play a role in providing these benefits.